2009
DOI: 10.1007/s10147-009-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer in endometriosis: molecular biology, pathology, and clinical management

Abstract: Recent molecular and pathological evidence suggests that endometriosis is a monoclonal, neoplastic disease. Moreover, endometriosis serves as a precursor of ovarian cancer (endometriosis-associated ovarian cancer; EAOC), especially of the endometrioid and clear cell subtypes. Although a variety of molecular events, such as p53 alteration, PTEN silencing, K-ras mutations, and HNF-1 activation, have been identified in EAOC, its precise carcinogenic mechanism remains poorly understood. Our recent data indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 69 publications
2
126
0
2
Order By: Relevance
“…It suggests that cortical inclusion cysts formed by invagination of ovarian surface epithelium serve as precursor lesions. The second theory involves the secondary müllerian system, suggesting müllerian-originated extraovarian lesions such as endometriosis as precursors of ovarian cancer (3)(4)(5)(6). The most recent theory suggests that intraepithelial lesions at fallopian tube fimbrial ends, enriched with TP53 somatic mutations or from BRCA1 carriers (7,8), serve as precursors of high grade serous ovarian cancer (9 -12), and thus epithelial ovarian cancer shares a common origin with distal fallopian tube cancer.…”
mentioning
confidence: 99%
“…It suggests that cortical inclusion cysts formed by invagination of ovarian surface epithelium serve as precursor lesions. The second theory involves the secondary müllerian system, suggesting müllerian-originated extraovarian lesions such as endometriosis as precursors of ovarian cancer (3)(4)(5)(6). The most recent theory suggests that intraepithelial lesions at fallopian tube fimbrial ends, enriched with TP53 somatic mutations or from BRCA1 carriers (7,8), serve as precursors of high grade serous ovarian cancer (9 -12), and thus epithelial ovarian cancer shares a common origin with distal fallopian tube cancer.…”
mentioning
confidence: 99%
“…These gene profiles might distinguish between cancers in a validation series of cEOC versus other histological types. Recently, Mandai et al has reported that the classification of the genes represents those involved in oxidative stress and inflammation, indicating that this cancer specifically expresses stress-response genes (14). These data allow us to speculate that retrograde menstruation or ovarian hemorrhage carries highly pro-oxidant factors, such as heme and iron, into the peritoneal cavity or ovarian endometrioma.…”
Section: Specific Expression Of Stress-related Genes In Ceocmentioning
confidence: 82%
“…Severe hemolysis occurring during the development of endometriosis results in high levels of free iron (14,22). Several important endometriosis-specific genes overlap with those known to be regulated by iron (8).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed an increased number of chromatid breaks in patients with endometriosis compared with those with ovarian cancer. Endometriosis is considered an important site of origin for ovarian cancer, and many molecular events observed in endometriosis (PTEN silencing, P53 alteration, and KRAS mutations) occur during ovarian cancer development [reviewed by Mandai et al (2009)]. Prowse et al (2006) analyzed the association between endometriosis and ovarian cancers using 82 microsatellite markers spanning the genome, to examine the loss of heterozygosity (LOH) in coexisting disease samples.…”
Section: Discussionmentioning
confidence: 99%